2015
DOI: 10.1007/978-3-319-26925-2_10
|View full text |Cite
|
Sign up to set email alerts
|

Radio-Aware Service-Level Scheduling to Minimize Downlink Traffic Delay Through Mobile Edge Computing

Abstract: Abstract. One of the most challenging problems in mobile broadband networks is how to assign the available radio resources among the different mobile users. Traditionally, research proposals are either specific to some type of traffic or deal with computationally intensive algorithms aimed at optimizing the delivery of general purpose traffic. Consequently, commercial networks do not incorporate these mechanisms due to the limited hardware resources at the mobile edge. Emerging 5G architectures introduce cloud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The authors design an optimal computation task scheduling policy for MEC systems. The delay of general traffic flows in the LTE downlink can be minimized by service level scheduling via MEC server deployed at the eNodeB [58]. Fog also provides low delay but with low capacity limitation, while the combined operation of fog and cloud can minimize the service latency and guarantee the capacity requirements at the same time [55].…”
Section: A Objectivesmentioning
confidence: 99%
“…The authors design an optimal computation task scheduling policy for MEC systems. The delay of general traffic flows in the LTE downlink can be minimized by service level scheduling via MEC server deployed at the eNodeB [58]. Fog also provides low delay but with low capacity limitation, while the combined operation of fog and cloud can minimize the service latency and guarantee the capacity requirements at the same time [55].…”
Section: A Objectivesmentioning
confidence: 99%
“…The MEC, initially introduced by IBM and Nokia Siemens Network, aims at optimizing the existing mobile infrastructure service, and minimizing the mean delay of general traffic flow in the LTE downlink [11]. Due to its characters of low latency, on-premises, and location awareness, MEC is introduced into the proposed architecture to improve the responsiveness for traffic light control and accident rescue.…”
Section: Mobile-edge Computing Server Layermentioning
confidence: 99%
“…In order to exemplify the expected performance improvements of the proposed solution, preliminary simulation studies have demonstrated the associated benefits for the problem of general flow scheduling [29] and for multimedia delivery [30] in multi-user scenarios.…”
Section: Conclusion and Further Workmentioning
confidence: 99%